2016
DOI: 10.1103/physreva.93.012101
|View full text |Cite
|
Sign up to set email alerts
|

Equivalence between divisibility and monotonic decrease of information in classical and quantum stochastic processes

Abstract: The crucial feature of a memoryless stochastic process is that any information about its state can only decrease as the system evolves. Here we show that such a decrease of information is equivalent to the underlying stochastic evolution being divisible. The main result, which holds independently of the model of the microscopic interaction and is valid for both classical and quantum stochastic processes, relies on a quantum version of the so-called Blackwell-Sherman-Stein theorem in classical statistics.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
107
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(109 citation statements)
references
References 48 publications
2
107
0
Order By: Relevance
“…Once ρ 1 and ρ 2 are determined, by setting the initial tripartite state introduced in Eqs. (16)(17) as…”
Section: Appendix F: Eternally Non-markovian Qubit Dynamicsmentioning
confidence: 99%
“…Once ρ 1 and ρ 2 are determined, by setting the initial tripartite state introduced in Eqs. (16)(17) as…”
Section: Appendix F: Eternally Non-markovian Qubit Dynamicsmentioning
confidence: 99%
“…This interpretation is based on the following. The proof is given in appendix D. We expect that the network min-entropy defined in equation (45) will play a role in the study non-Markovian quantum evolutions, along the lines of the entropic characterization of Markovianity provided in [89,90]. Intuitively, the idea is that one can evaluate how the correlations build up from one step to the next and use this information to infer properties of the internal memory used by the network.…”
Section: The Conditional Min-entropy Of a Quantum Causal Networkmentioning
confidence: 99%
“…This question was answered already in 1953 by Blackwell [7] for the classical case, and in 1980 by Alberti and Uhlmann [8] for the qubit case. More recently, it was solved for pure states in [9], characterized in [10], [11], [12], [13], and finally, in [14] it was fully solved (for finite dimensions) with semidefinite programming. In [14], [15] (see also references therein) it was also shown that this pre-order can be characterized completely in terms of a family of distinguishability measures that are given in terms of the conditional min-entropy [16], [17].…”
Section: Introductionmentioning
confidence: 99%